Banana seed genetic resources for food security: Status, constraints, and future priorities. (15th November 2021) - Kallow, Simon; Mertens, Arne; Janssens, Steven B.; Vandelook, Filip; Dickie, John; Swennen, Rony; Panis, Bart
Abstract: Storing seed collections of crop wild relatives, wild plant taxa genetically related to crops, is an essential component in global food security. Seed banking protects genetic resources from degradation and extinction and provides material for use by breeders. Despite being among the most important crops in the world, banana and plantain crop wild relatives are largely under‐represented in genebanks. Nevertheless, banana crop wild relative seed collections are in fact held in different countries, but these have not previously been part of reporting or analysis. To fill this gap, we firstly collated banana seed accession data from 13 institutions in 10 countries. These included 537 accessions containing an estimated 430, 000 seeds of 56 species. We reviewed their taxonomic coverage and seed storage conditions including viability estimates. We found that seed accessions have low viability (25% mean) representing problems in seed storage and processing. Secondly, we surveyed 22 institutions involved in banana genetic resource conservation regarding the key constraints and knowledge gaps that institutions face related to banana seed conservation. Major constraints were identified including finding suitable material and populations to collect seeds from, lack of knowledge regarding optimal storage conditions and germination conditions. Thirdly, we carried out a conservation prioritization and gap analysis of Musaceae taxa, using established methods, to index representativeness. Overall, our conservation assessment showed that despite this extended data set banana crop wild relatives are inadequately conserved, with 51% of taxa not represented in seed collections at all; the average conservation assessment showing high priority for conservation according to the index. Finally, we provide recommendations for future collecting, research, and management, to conserve banana and plantain crop wild relatives in seed banks for future generations. Abstract : Over 430, 000 seeds of 56 banana crop wild relative taxa are stored in 13 institutions in 10 countries. Despite this, most taxa are inadequately conserved in seed banks and they remain high priority for conservation. We identify major constraints to their conservation and make recommendations for future management, research and collection.